Latihan asertif dengan metode roleplay untuk meningkatkan perilaku asertif pada anak korban perundungan - Nadhifa Salsabillah Riyadi; Yudi Suharsono (Universitas Muhammadiyah Malang, 2026)
Assertive behavior enables individuals to express feelings honestly and defend themselves without harming others. The subject of this case study is a 9-year-old girl who had not yet demonstrated assertive behavior when facing physical and verbal bullying. Consequently, the subject tended to be passive and experienced physical complaints such as stomach aches. Data were collected through interviews, observations, and the Wechsler Intelligence Scale for Children (WISC). The intervention employed was the role-play method to increase the subject’s assertive behavior. Results indicate that the role-play method was effective in enhancing the subject’s ability to act according to her own desires, express feelings honestly, and comfortably defend her personal rights. This increase in assertiveness also led to a decrease in the frequency of bullying experienced by the subject